Kualitas dan Keberhasilan Lulusan Prodi IAN FIS UNP dalam Mendapatkan Pekerjaan - Syamsir Syamsir; Heni Candra Gustina (Faculty of Social Science, Universitas Negeri Padang, 2017)
This study aims to describe the success of Prodi IAN FIS UNP graduates in getting a job and to identify the factors determining the success of the graduates in finding employment. This research was conducted through quantitative and qualitative approaches. Data collected through questionnaires, interviews, and documentation on several private and government agencies in the province of West Sumatra where the alumni of Prodi IAN work. To obtain quantitative data the researchers used a technique of proportional sampling area through the tracer study. As for the qualitative data, the informant has been determined purposively. Qualitative data were analyzed through interactive models of analysis. While quantitative data were analyzed through descriptive statistical analysis in the form of frequency, percentage, and mean. The results of this study, among others, indicate that the sustainability of a study program depends not only on the ability of managers to manage the institution, but should also consider the needs of other stakeholders interested in the study program that is students, alumni, and the workforce.